Influence of small DC bias field on the electrical behaviour of Sr- and Mg-doped lanthanum gallate - Raghvendra; Singh R.K.; Singh P. (My University, 2025)
One of the promising electrolyte materials for solid oxide fuel cells application, Sr- and Mg-doped lanthanum gallate La0.9Sr 0.1Ga0.8Mg0.2O3-δ (LSGM), is synthesized by conventional solid state ceramic route. X-ray Rietveld analysis confirms the formation of main orthorhombic phase at room temperature along with a few minor secondary phases. SEM micrograph reveals the grain and grainboundary morphology of the system. Electrical conductivity of the LSGM sample is measured in the temperature range 573-873 K and in the frequency range 20 Hz-1 MHz at a few small DC bias fields (at 0.0, 0.5, 1.0, 1.5 and 2.0 V). The conductivity spectra show power-law behaviour. Electrical conductivity of the sample is found to be weakly dependent on DC bias field. This is attributed to field-dependent bulk and grainboundary conduction processes. In the present system, under investigated bias field range, the possibility of formation of Schottky barrier is ruled out. The concept of grainboundary channel (pathway) modulation on the application of bias field is proposed. © 2014 Springer-Verlag Berlin Heidelberg.